Pengaruh Gaya Hidup, Financial Literacy dan Pendapatan Terhadap Pengelolaan Keuangan Mahasiswa Akuntansi Universitas Hindu Indonesia - Ni Luh Made Rima Novitayanti; Putu Nuniek Hutnaleontina; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2026)
The low level of financial literacy among the younger generation indicates that students do not yet possess sufficient knowledge to manage their finances wisely. Although there has been some progress, it has not been fully matched by an adequate understanding of accounting. Financial management is influenced by many factors, such as lifestyle, financial literacy and income. This study aims to determine the influence of lifestyle, financial literacy and income on financial management. The research was conducted at the Indonesian Hindu University and involved 82 respondents. The data analysis techniques used were Validity and Reliability Tests, Classical Assumptions, Multiple Linear Regression, F-Test, t-Test and Coefficient of Determination. The findings show that lifestyle has a positive and significant influence on financial management, financial literacy has a positive and significant influence on financial management, and income has a positive and significant influence on financial management. The magnitude of the influence of the independent variables on financial management is 65%. Therefore, it is recommended that accounting students at the University of Hindu Indonesia are expected to always manage their lifestyle well, improve their financial literacy through academic learning or financial seminars, and increase their income by seeking additional work opportunities